Strays [videorecording (DVD)] - Perrault, Dan; Gelman, Brett, 1976-; Forte, Will (Universal, 2023)
They say a dog is a man's best friend, but what if the man is a total dirtbag? In that case, it might be time for some sweet revenge, doggy style. When Reggie, a naive, relentlessly optimistic Border Terrier, is abandoned on the mean city streets by his lowlife owner, Doug, Reggie is certain that his beloved owner would never leave him on purpose. But once Reggie falls in with a fast-talking, foul-mouthed Boston Terrier named Bug, a stray who loves his freedom and believes that owners are for suckers, Reggie finally realizes he was in a toxic relationship and begins to see Doug for the heartless sleazeball that he is. Determined to seek revenge, Reggie, Bug, and Bug's pals Maggie, a smart Australian Shepherd who has been sidelined by her owner's new puppy, and Hunter, an anxious Great Dane who's stressed out by his work as an emotional support animal together hatch a plan and embark on an epic adventure to help Reggie find his way home ... and make Doug pay by biting off the appendage he loves the most. (Hint: It's not his foot.).